Hydralazine versus Labetalol for acute control of blood pressure in patients with severe pre-eclampsia: a randomized controlled trial - Gaur, Nayanika; Kathuria, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Authors sought to compare the effectively of intravenous hydralazine and intravenous labetalol in controlling acute rise in blood pressure in patients with severe preeclampsia. Methods: In this double-blind randomized controlled trial, all pregnant women with sustained increase in blood pressure (BP) of 160 mmHg systolic or 110 mmHg diastolic or higher were randomized to receive intravenous (IV) hydralazine 5 mg (max. 4 doses) or IV labetalol in escalating doses of 20mg, 40mg, 80mg, 80mg to achieve target blood pressure of 150 mmHg systolic and 100 mmHg diastolic or lower. The primary objective of the study was to assess the time taken to control blood pressure. Secondary agendas were the number of repeat doses required and other side effect profile. Results: In the study duration of September 2015 to September 2017, authors enrolled 60 participants for our trial. The median time taken to achieve the target blood pressure was 22.4 minutes in both the groups. Close to half of the participants did not require repeat doses (46.66% with labetalol and 50% with hydralazine). No serious maternal or foetal side effects were noted during the study. Statistical tests were performed using SPSS for Windows version 22. Conclusions: As operated in the study, the efficacy of hydralazine and labetalol to control the acute rise in blood pressure is similar.